1978
DOI: 10.1111/j.1744-6570.1978.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Impression Characteristics of the Recruitment Interviewer

Abstract: Students' impressions of campus recruiters influence students decisions on eventual job choice. In this study, the authors attempted to assess the effects of three variables—recruiter's age, recruiter's title, and recruiter's presentation—on students' impressions. A three factor factorial analysis of variance with three separate post hoc tests indicated that recruiter title and recruiter age significantly influenced impressions, while nonfluent presentation may have had a selective influence on impressions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…and Sincoff (1978) found that a recruiter's title influenced students' impressions of a college recruitment interviewer.…”
Section: Interviewer Characteristicsmentioning
confidence: 99%
“…and Sincoff (1978) found that a recruiter's title influenced students' impressions of a college recruitment interviewer.…”
Section: Interviewer Characteristicsmentioning
confidence: 99%
“…This study indicated that the interviewer's personality, manner of delivery, and presentation of job information had a significant effect on the applicant's decision to seek/accept employment in that organization. Rogers and Sincoff (1978) Good recruiter presentations were smooth and fluent. Poor recruiter presentations included 50 performance difficulties with hesitations, mispronunciations, and extended pauses.…”
Section: Recruiter Effectsmentioning
confidence: 99%
“…The importance of the interview in the organization's attempt to recruit top candidates motivated researchers to investigate interviewer behaviors such as personableness, competence, informativeness aggressiveness, and gender, relative to the applicant's expectancy of receiving a job offer and probability of accepting the job offered (Harris & Fink, 1987). Rogers and Sincoff (1978) found a significance in the recruiter's age, title, and manner of presentation on applicant decisions to accept a job offer.…”
Section: Recruiter Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviewees formed an overall impression of the goodness or badness of an interviewer and that this was an important factor in the employment decision they made. Rogers and Sincoff (1978) determined if the effects of three variables (recruiter age, recruiter title, and recruiter presentation) had an effect on job applicants.…”
Section: The Researchers Used Multiple Regression Analysis Tomentioning
confidence: 99%